Knowledge of Family About Post Stroke Care for the Elderly in Kasang Kumpeh Village Jambi - Mawaddah Warahmah (CV Media Inti Teknologi, 2023)
The elderly period or aging process is bound to occur in the human condition. Various types of diseases are very easy to attack the function of our organs. To minimize the disease that comes, a good lifestyle is needed by means of routine exercise and knowledge about health awareness. Stroke is a common cause of third-order death in developed countries after cardiovascular disease and cancer. The goal of rehabilitation is to help patients become independent again and have a good quality of life. This research activity is to determine the description of family knowledge about care for the elderly or post patients in Kasang Kumpeh Village, because stroke is one of the diseases that requires special care and support from the family. The method used in this study is qualitative method and the technique carried out is sampling technique. The results showed that family knowledge about post-stroke patients was mostly lacking. The more knowledge the family has, the greater the support that can be provided in the process of treating stroke patients. Furthermore, this research can be used as a source of family knowledge for post-stroke therapy for the elderly in Kasang Kumpeh village. The results of the evaluation both through interviews, questions and answers regarding post-stroke knowledge are that the average family and the elderly each know less about the care of post-stroke patients, so it is necessary to hold further eduaction related to this post-stroke.